The role of technology as an absorptive capacity in economic growth in emerging economies: A new approach - Richard Angelous Kotey; Joshua Yindenaba Abor (The European Journal of Applied Economics, 2019)
Studies have shown that the effects of Foreign Direct Investment (FDI) on economic growth have not always been direct, especially in developing regions; certain characteristics must exist in the economy for the effects of FDI to be well absorbed. Therefore, this study sought to assess the economic impact of FDI on economic growth in Sub-Saharan African (SSA) countries, factoring in technology as an absorptive capacity. Because of the scarcity of data on a viable proxy for technology in the African context, we measure technology in a novel approach, using annual number of published innovation-related papers as a proxy for technological presence. Data from forty-three Sub-Saharan countries over a 19-year period (from 1990 to 2008) was analyzed. Using a Fixed Effects (FE) regression model, the study found that FDI had a negative and significant effect on GDP, which is our proxy for economic growth. However, when FDI is interacted with technology, the relationship turns positive and significant. This implies that countries with technological presence are more able to absorb from FDI than those with little technology. Furthermore, the study found that countries with high technology were able to absorb more from FDI than those with low technology. – – Istraživanja su pokazala da efekti direktnih stranih investicija na ekonomski rast nisu uvek bili neposredni, posebno ne u oblastima koje se razvijaju; potrebno je da u samoj privredi već postoje odreene osobenosti, a kako bi se navedeni efekti pravilno absorbovali. Otuda, ovo istraživanje je imalo za cilj da proceni ekonomski uticaj direktnih stranih investicija na ekonomski rast zemalja Supsaharske Afrike, uzimajuc'i u obzir tehnologiju kao apsorpcioni kapacitet. Zbog nedostatka podataka o održivom merilu, a kada je u pitanju tehnologija iz perspektive Afrike, promeravamo tehnologiju uz upotrebu inovativnog pristupa, koristeći godišnji broj objavljenih radova u vezi sa inovacijama, kao merilo tehnološkog prisustva. Analizirani su podaci iz četrdeset tri supsaharske zemlje, koji ilustruju period od 19 godina (od 1990. do 2008). Upotrebom regresionog modela fiksnih efekata (Fixed Effects), istraživanje je pokazalo da direktne strane investicije imaju negativan i značajan uticaj na bruto domaći proizvod (BDP), što je naš parametar za ekonomski razvoj. Ipak, kada se investicije udruže sa tehnologijom, ovaj odnos postaje značajan i pozitivan. Navedeno pokazuje da zemlje u kojima je tehnologija razvijenija lakše prihvataju i koriste strane direktne investicije, u odnosu na zemlje u kojima je tehnologija slabije razvijena.
Keywords: C23; O47; F23; O11; 330; Foreign Direct Investment; Technology; Innovation; Absorptive Capacity